0110 Cancer Mortality among Styrene and Fibreglass Exposed Workers in the Reinforced Plastic Boatbuilding Industry. (23rd June 2014) - Ruder, Avima; Meyers, Alysha; Bertke, Steven
Abstract : Objectives: Mortality was updaated through 2008 for 5203 workers exposed to styrene, fibreglass, and wood dust between 1959 and 1978 at two boatbuilding plants. The a priori hypothesis: leukaemia and lymphoma excesses would be found Method: Standardised mortality ratios (SMR), standardised rate ratios (SRR), and 95% confidence intervals (CI) were calculated using Washington State rates and a person-years analysis program, LTAS. NET, controlling for age, calendar period, race, and gender. The SRR analysis compared tertiles of estimated cumulative styrene exposure. Results: Overall, 484 cancer deaths occurred (SMR 1.20, CI 1.10–1.31), with excess mortality for respiratory cancers (n = 171, SMR 1.33, CI 1.14–1.55) and prostate cancer (n = 41, SMR 1.44, CI 1.03–1.96). Among 2063 workers highly exposed to styrene and fibreglass there were excesses of mesothelioma (n = 3, SMR 5.28, CI 1.09–15.4) and ovarian cancer (n = 6, SMR 2.94, CI 1.08–6.41). The SRR analysis did not find strong associations between tertiles of styrene exposure and cancer mortality. Conclusions: We found no excess leukaemia or lymphoma mortality. Unanticipated excess mesothelioma and ovarian cancer mortality are difficult to interpret and could be due to fibreglass exposure or employment elsewhere, or could be chance findings.